Analysis of Eimeriostatic Drugs Tested on Experimental Chickens With Eimeriosis - Xudjamshukurov; Nurmamatovich, Akhtam (American Journal of Biology and Natural Sciences, 2026)
The data of efficacy of coccidiostatics of toltrox, cigro, amprolin and its combination with vitamin complex in experimental eimeriosis in birds have been presented.